Towards intercultural learning PERMIT's learned lessons and the future - Umberto Margiotta; Juliana Raffaghelli (Pensa MultiMedia, 2015)
In the context of globalization, as we have demonstrated in this case study so far, intercultural education is receiving much interest. Connected to this, there has been a raising number of cultural studies, cross cultural approaches, as well as interventions to promote intercultural dialogue as part of a new mode of thinking education for the multiethnic society. In fact, culture has become an instrument for social interpretation and communicative action. As it has been emphasised in this book, the main goal of intercultural education is seen as the development of intercultural competence, which is the ability to act and relate appropriately and effectively in various cultural contexts. Intercultural competence is generally thought to require three components on the learner's side: a certain skillset, culturally sensitive knowledge, and a motivated mindset.